Fiber sheet and method for producing the same
Patent Information
- Application Number
- JP2023133898
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-21
- Publication Date
- 2025-03-06
AI Technical Summary
【0010】 本発明の繊維シートはナノ繊維本来の特性を損なうことなく、プリーツ加工などの耐加工性に優れる。また、ナノ繊維シートと保護繊維シートとの密着性に優れるため、多孔層と積層して繊維シートとする際に、接着加工やカレンダー加工などの一体化工程を経ることなく高い生産性と良好な操業性で繊維シートを提供することができる。
Smart Images

Figure 2025029341000001 
Figure 2025029341000002 
Figure 2025029341000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a fiber sheet containing nanofibers and a method for producing the same. [Background technology]
[0002] In recent years, ultrafine fibers having a diameter of several to several hundred nanometers (nm), so-called nanofibers, have been attracting attention. Nanofibers have characteristics such as a large specific surface area per se, small interfiber voids in fiber sheets containing nanofibers, and a uniform void size distribution, and are therefore expected to be applied to filter media, sound absorbing materials, masks, waterproof and moisture permeable membranes, secondary battery separators, sensor materials, cell culture substrates, and the like. Among these, nanofibers made of polyvinylidene fluoride polymers have excellent properties such as mechanical strength, heat resistance, chemical resistance, and processability into nanofibers, and therefore can be applied to a wide range of fields.
[0003] Electrostatic spinning is known as a method for producing nanofibers. In a typical electrostatic spinning method, a spinning solution in which a polymer is dissolved is charged with a high voltage together with a metallic spinning nozzle, and the solution is discharged from the tip of the spinning nozzle toward the surface of a grounded collecting electrode to form droplets. The droplets are attracted to the surface of the collecting electrode by a strong electrostatic force at the tip of the spinning nozzle, and the spinning solution flies as a jet, thinning with the evaporation of the solvent, and nanofibers with a diameter of several to several hundred nm are collected to form a nonwoven nanofiber sheet. The electrostatic spinning method can nanofiberize a wide range of materials, and can make the fibers extremely fine and uniform. However, since the diameter of the nanofibers obtained is small and the mechanical strength per fiber is low, the surface of the nanofiber sheet is subject to frictional forces when it comes into contact with a processing device, causing single thread breakage and nonwoven fabric tearing, and the processability is reduced due to the low rigidity of the nanofiber sheet.
[0004] In response to these problems, a method of laminating and integrating a nanofiber sheet with a porous layer having excellent strength and rigidity has been proposed (for example, Patent Document 1). Patent Document 1 discloses a laminate in which a nonwoven fabric produced by electrospinning and a breathable sheet are bonded and integrated with an adhesive, and the penetration depth of the adhesive from the surface of the nonwoven fabric in the thickness direction of the nonwoven fabric is 40% or less of the thickness of the nonwoven fabric. However, although such a laminate improves the adhesive strength between the layers, the adhesive penetrates into the interfiber voids and blocks the pores, so that the inherent properties of the nanofibers are not fully exhibited. In addition, during the hot press during pleating, the adhesive seeps out onto the surface of the fiber material, causing the surfaces to bond together and making it impossible to form pleats, or dissolves into the liquid or air, polluting the environment. Furthermore, since the process includes a step of integrating a nonwoven fabric produced by electrospinning and a breathable sheet with an adhesive, there are problems in that stable operability cannot be obtained and sufficient productivity cannot be obtained.
[0005] The applicant has previously proposed a fiber sheet obtained by spinning a polyvinylidene fluoride-based copolymer mainly composed of vinylidene fluoride by an electrospinning method and collecting the spun fibers, the fibers constituting the fiber sheet having an average fiber diameter of 20 nm or more and less than 1000 nm, a melting temperature of the fiber sheet being 155° C. or more and a heat of fusion of 45 J / g or less in a DSC measurement (Patent Document 2). According to this method, the fiber sheet can be well integrated with other materials without significant shrinkage due to changes over time or heating during molding into products, but when processed into products, problems may arise such as fluffing due to contact between the fiber sheet and rolls and deformation or tearing of the surface of the nanofiber sheet during pleating. Patent Document 3 proposes the introduction of a protective layer or an adhesive layer to avoid performance deterioration of the fiber sheet during the processing process. However, the use of a protective layer or adhesive layer can increase pressure loss and deteriorate the performance of the fiber sheet itself, and the methods of Patent Documents 2 and 3 leave room for improvement in terms of the problem of deformation and tearing of the surface of the nanofiber sheet during processing. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2007-30175 A [Patent Document 2] JP 2015-45114 A [Patent Document 3] JP 2015-57950 A Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention aims to solve the above-mentioned problems, reduce deformation and tearing of the surface of a nanofiber sheet without compromising the inherent properties of the nanofibers during pleating, and provide a fiber sheet that has excellent performance even after pleating. [Means for solving the problem]
[0008] The present inventors have conducted extensive research to solve the above problems, and as a result, have found that the above problems can be solved by forming a fiber sheet in which a protective fiber sheet having specific physical properties is laminated between a nanofiber sheet and a porous layer, thereby completing the present invention.
[0009] That is, the present invention has the following configuration. [1] A fiber sheet comprising a nanofiber sheet containing nanofibers, a protective fiber sheet containing protective fibers, and a porous layer laminated in this order, wherein the nanofibers have an average fiber diameter of 20 to 1000 nm, and the polymer constituting the protective fibers satisfies at least one selected from the following (1) to (3): (1) Rockwell hardness R110 or less (2) Shore hardness A100 or less (3) Shore hardness D70 or less [2] The fiber sheet according to [1], wherein the polymer constituting the protective fiber includes at least one polymer selected from a thermoplastic urethane polymer, a thermoplastic urea polymer, and a vinyl acetal polymer. [3] The fiber sheet according to [1] or [2], wherein the polymer constituting the nanofibers includes a vinylidene fluoride polymer. [4] The fiber sheet according to any one of [1] to [3], wherein the protective fibers have an average fiber diameter of 20 to 5,000 nm. [5] The fiber sheet according to any one of [1] to [4], comprising two or more layers of the nanofiber sheet. [6] A method for producing a fiber sheet according to any one of [1] to [5], comprising the steps of electrostatically spinning the protective fiber sheet on the porous layer, and electrostatically spinning a nanofiber sheet on the protective fiber sheet. [7] A method for producing a fiber sheet according to [6], further comprising a step of heat treating the nanofiber sheet with circulating hot air or radiant heat after the step of electrostatically spinning the nanofiber sheet. [8] A filter medium comprising the fiber sheet according to any one of [1] to [5]. Effect of the Invention
[0010] The fiber sheet of the present invention has excellent resistance to processing such as pleating without impairing the inherent properties of the nanofibers. In addition, since the nanofiber sheet and the protective fiber sheet have excellent adhesion to each other, when the nanofiber sheet is laminated with a porous layer to form a fiber sheet, the fiber sheet can be provided with high productivity and good operability without going through an integration process such as bonding or calendaring. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in detail below.
[0012] The fiber sheet of the present invention is a laminate comprising a nanofiber sheet containing nanofibers having an average fiber diameter of 20 to 1000 nm, a protective fiber sheet containing protective fibers, and a porous layer, laminated in this order, and is characterized in that the polymer constituting the protective fiber is a polymer satisfying at least one selected from a Rockwell hardness of R110 or less, a Shore hardness of A100 or less, and a Shore hardness of D70 or less. By using this configuration, it is possible to obtain a fiber sheet with excellent adhesion between the nanofiber sheet and the porous layer, without compromising the inherent properties of the nanofibers during pleating, without deformation or tearing of the nanofiber surface, and with high productivity and good operability.
[0013] <Nanofiber sheet> The nanofiber sheet of the present invention contains nanofibers with an average fiber diameter of 20 to 1000 nm. If the average fiber diameter of the nanofibers is 1000 nm or less, the specific surface area is large, and the characteristics derived from the nanofibers, such as excellent filtering performance, are easily exhibited, while if the average fiber diameter is 20 nm or more, the single fiber strength is satisfactory, and breakage and fluffing of the nanofibers during processing into products can be suppressed. From this viewpoint, the average fiber diameter is preferably 30 to 600 nm, and more preferably 50 to 300 nm.
[0014] The polymer constituting the nanofiber in the present invention is not particularly limited, and examples thereof include vinylidene fluoride polymer, polyvinyl alcohol, polyethylene glycol, polyethylene oxide, polyacrylic acid, polyvinylpyrrolidone, polyethylene, polypropylene, cyclic polyolefin, polyethylene terephthalate, polybutylene terephthalate, polylactic acid, polyglycolic acid, polycaprolactone, polybutylene succinate, nylon 6, nylon 6,6, aromatic polyamide, polyurethane, polycarbonate, polystyrene, polysulfone, polyethersulfone, polyacrylonitrile, polymethyl methacrylate, cellulose, cellulose acetate, collagen, glucomannan derivatives, chitin, chitosan, polylysine, polyamic acid, polyimide, polyvinyl formal, and mixtures thereof. From the viewpoint of high water repellency and stain resistance of the nanofiber surface, however, vinylidene fluoride polymer is preferable. The vinylidene fluoride polymer may be a vinylidene fluoride homopolymer or a vinylidene fluoride-based copolymer, or may be a mixture of a vinylidene fluoride homopolymer and a vinylidene fluoride-based copolymer.
[0015] When the polymer constituting the nanofiber is a mixture of vinylidene fluoride homopolymer and vinylidene fluoride copolymer, it is possible to combine the characteristics of vinylidene fluoride homopolymer, which has excellent durability such as chemical resistance and heat resistance, and can form thin and uniform fibers, with the characteristics of vinylidene fluoride copolymer, which is flexible, suppresses fluffing and interlayer peeling between fiber sheets, and has excellent adhesion to other materials. Here, vinylidene fluoride homopolymer means a polymer polymerized substantially only from vinylidene fluoride monomer. Furthermore, vinylidene fluoride copolymer means a copolymer of vinylidene fluoride and other monomers, and examples thereof include copolymers of vinylidene fluoride and fluorine-based monomers such as trifluoroethylene, tetrafluoroethylene, or hexafluoropropylene. Among them, from the viewpoint of suppressing fluffing and interlayer peeling between fiber sheets and improving adhesion to other materials, a copolymer of vinylidene fluoride and hexafluoropropylene is preferable. The copolymer may be a random copolymer or a block copolymer, but is preferably a random copolymer from the viewpoints of suppressing fuzzing and delamination between fiber sheets and improving adhesion to other materials.
[0016] The melting point of the vinylidene fluoride homopolymer is not particularly limited to an upper limit as long as it is a temperature at which it does not melt during thermal processing, but in terms of ease of dissolution in a solvent, it is preferably 180°C or less, more preferably 175°C or less. On the other hand, in terms of increasing heat resistance during processing, the melting point is preferably 155°C or more, more preferably 160°C or more, and even more preferably 165°C or more. If the melting point of the vinylidene fluoride homopolymer is 155°C or more, it is excellent in durability such as chemical resistance and heat resistance. In addition, the melting point of the vinylidene fluoride copolymer is not particularly limited, but it is preferably 150°C or less, more preferably 135°C or less, and even more preferably 125°C or less. If the melting point of the vinylidene fluoride copolymer is 150°C or less, it is possible to suppress fluffing and delamination between fiber sheets and improve adhesion to other materials. On the other hand, the lower limit of the melting point of the vinylidene fluoride copolymer is not particularly limited, but is preferably at least 60° C., more preferably at least 80° C., and even more preferably at least 100° C. If the melting point is at least 60° C., the nanofibers are less likely to melt even when processed under high temperature conditions during processing into products, and the inherent properties of the nanofibers are more likely to be maintained.
[0017] The mixing ratio (weight ratio) of the vinylidene fluoride homopolymer and the vinylidene fluoride copolymer is not particularly limited, but is preferably 50:50 to 95:5, more preferably 60:40 to 93:7, and even more preferably 75:25 to 92.5:7.5. If the mixing ratio (weight ratio) is 50:50 or more, durability such as chemical resistance and heat resistance is excellent, and thin and uniform fibers are easily obtained, and if it is 95:5 or less, fluffing and delamination are suppressed, and adhesion to other materials is excellent.
[0018] The weight-average molecular weight of the vinylidene fluoride polymer is not particularly limited, but is preferably 100,000 to 1,000,000, and more preferably 200,000 to 800,000. If the weight-average molecular weight is 100,000 or more, the formability of nanofibers is excellent, and if it is 1,000,000 or less, the solubility and thermoplasticity are excellent, and processing is easy.
[0019] The melt viscosity of the vinylidene fluoride homopolymer is not particularly limited, but is preferably measured in accordance with ASTM D3835 at a melt temperature of 232° C. and a shear rate of 100 sec -1 In the above, the melt viscosity is preferably 2 to 60 kpoise, more preferably 10 to 50 kpoise, and further preferably 20 to 40 kpoise. The melt viscosity of the vinylidene fluoride copolymer is not particularly limited, but is preferably 20 to 40 kpoise at a melting temperature of 232° C. and a shear rate of 100 sec , as measured in accordance with ASTM D3835. -1 In this case, the viscosity is preferably 0.5 to 35 kpoise, more preferably 2 to 30 kpoise, and further preferably 5 to 20 kpoise.
[0020] The nanofibers may contain, but are not limited to, a conductive agent. When the nanofibers contain a conductive agent, the nanofibers become extremely fine, and the generation of beads is suppressed, resulting in homogeneous nanofibers, which makes it easier to exhibit the inherent properties of the nanofibers. Furthermore, the nanofibers are strongly attracted toward the collector by the high voltage in the electrostatic spinning process described below, and are densely collected, improving the adhesion between the nanofibers themselves or between the nanofibers and other materials, thereby suppressing fluffing and delamination. Examples of the conductive agent include anionic surfactants such as sodium dodecyl sulfate, cationic surfactants such as tetrabutylammonium bromide, and organic or inorganic salts. As long as the concentration of the conductive agent is 0.1 to 10% by weight relative to the weight of the nanofibers, an effect commensurate with the use can be obtained.
[0021] The nanofibers may be provided with a water repellent, although there is no particular limitation. By providing the water repellent, the water repellency of the nanofibers is improved, the deterioration of properties due to water absorption or moisture absorption is suppressed, and the properties derived from the nanofibers can be maintained for a long period of time. The water repellent is not particularly limited as long as it can provide water repellency to the nanofibers, and examples of the water repellent include fluorine group-containing oligomers, fluorine group-containing polymers, fluorine-based surfactants having perfluoroalkyl groups, fluorine-based surfactants having perfluoroalkenyl groups, silicone oligomers, silicone polymers, silicon-based silane compounds, fluorine-based silane compounds, fluorine-containing cage-type silsesquioxanes, fluorine-modified polyurethanes, and silicon-modified polyurethanes. Among them, it is preferable to use water repellents containing fluorine, such as fluorine group-containing polymers, fluorine-containing cage-type silsesquioxanes, or fluorine-modified polyurethanes, from the viewpoints of water repellency, workability, and cost. The concentration of the water repellent is not particularly limited, but is preferably 0.1 to 20% by weight, more preferably 1 to 15% by weight, based on the nanofibers. If the concentration of the water repellent is 0.1% by weight or more, water repellency can be imparted to the nanofibers, and if the concentration is 20% by weight or less, an improvement in effect commensurate with the amount used can be obtained. The state in which the water repellent is applied is not particularly limited, and the water repellent may be mixed into the nanofibers or coated on the surface of the nanofibers. In addition, the method of applying the water repellent is not particularly limited, and the water repellent may be dispersed or dissolved in a spinning solution and then spun, or after obtaining the nanofibers, the water repellent may be applied using a known device or method such as a dipping method or a spray coating method.
[0022] The nanofibers are not particularly limited as long as they do not impair the effects of the present invention, and may contain polymer components, metal oxide components such as silica, alumina, titania, zirconia, yttrium-stabilized zirconia, barium titanate, or hydroxyapatite, hydrophilic materials, weather resistance agents, stabilizers, etc. These may be used alone or in combination of two or more. The concentrations of these components are not particularly limited, and may be 0.1 to 20% by weight based on the nanofibers.
[0023] The weight of the nanofiber sheet is not particularly limited, but is preferably 0.01 to 20 g / m in order to make it easier to exhibit the properties of the nanofiber. 2 It is preferable that the thickness is 0.1 to 5 g / m 2 More preferably, the density is 0.2 to 3 g / m 2 Furthermore, the thickness of the nanofiber sheet is not particularly limited, and is preferably 0.5 to 100 μm, more preferably 1 to 50 μm, and even more preferably 2 to 30 μm.
[0024] The nanofiber sheet may contain the above-mentioned nanofibers, and may contain nanofibers having different average fiber diameters and / or polymer components. Furthermore, fibers other than the above-mentioned nanofibers may be mixed within a range that does not impair the effects of the present invention. The mixing ratio is not particularly limited, and may be, for example, 1:10 to 10:1 by weight.
[0025] The fiber sheet of the present invention is not particularly limited, but preferably contains two or more nanofiber sheets. By containing two or more nanofiber sheets, the variation in physical properties of the nanofiber sheet can be reduced, so that the amount of nanofibers required to obtain the required characteristics can be reduced, and high productivity can be obtained. When containing two or more nanofiber sheets, there is no particular limitation as long as the above-mentioned nanofibers are contained, and each nanofiber sheet may contain the same nanofibers, or may contain nanofibers with different average fiber diameters or polymer components.
[0026] <Protective fiber sheet> The protective fiber sheet in the present invention is provided for the purpose of protecting the nanofiber sheet during processing, and contains protective fibers made of a polymer that satisfies at least one of the raw material resin's Rockwell hardness R110 or less, Shore hardness A100 or less, and Shore hardness D70 or less. By using such a polymer, the stress between the nanofiber sheet and the porous layer during processing can be alleviated, and deformation and tearing of the surface of the nanofiber sheet can be prevented.
[0027] The polymer constituting the protective fiber sheet in the present invention is not particularly limited, but preferably contains at least one polymer selected from thermoplastic urethane polymer, thermoplastic urea polymer, and vinyl acetal polymer. These polymers have a structure involved in hydrogen bonding in the molecule (urethane group of thermoplastic urethane polymer, urea group of thermoplastic urea polymer, hydroxyl group of vinyl acetal polymer, etc.), and therefore can impart flexibility as well as adhesion between the porous layer and the nanofiber sheet. The thermoplastic urethane polymer is not particularly limited, and examples thereof include ester-based polyurethane, ether-based polyurethane, lactone-based polyurethane, and carbonate-based polyurethane. The thermoplastic urea polymer is not particularly limited, and examples thereof include aliphatic polyurea or aromatic polyurea. The vinyl acetal polymer is not particularly limited, and examples thereof include polyvinyl acetoacetal, polyvinyl propional, polyvinyl butyral, and polyvinyl pentanal.
[0028] The average fiber diameter of the protective fiber in the present invention is not particularly limited, but is preferably 20 to 5000 nm, more preferably 20 to 3000 nm, and even more preferably 20 to 2000. When the average fiber diameter of the protective fiber is 20 nm or more, the shape of the protective fiber can be maintained, and when it is 5000 nm or less, the effect of pressure loss can be suppressed.
[0029] The protective fiber sheet may contain, within the range that does not impair the effects of the present invention, a conductivity imparting agent, a water repellent agent, a polymer component, a metal oxide component, a hydrophilic material, a weather resistance agent, a stabilizer, etc. The concentration of these components is not particularly limited, and may be 0.1 to 20% by weight relative to the protective fiber.
[0030] The basis weight of the protective fiber sheet is not particularly limited, but is preferably 0.1 to 5 g / m from the viewpoint of breathability of the fiber sheet. 2 It is preferable that the density is 0.1 to 2 g / m 2 More preferably, the density is 0.1 to 1.0 g / m 2Furthermore, the thickness of the protective fiber sheet is not particularly limited, and is preferably 0.1 to 50 μm, more preferably 0.1 to 30 μm, and even more preferably 0.1 to 20 μm.
[0031] <Porous layer> The porous layer in the present invention is provided to impart strength and rigidity to the nanofiber sheet. Such a porous layer is not particularly limited, and examples thereof include woven fabrics, knitted fabrics, nonwoven fabrics, papermaking, felt, nets, and microporous films, but nonwoven fabrics are preferred in terms of processability and availability. The nonwoven fabric is not particularly limited, and examples thereof include thermal bonded nonwoven fabrics, thermal calendared nonwoven fabrics, through-air nonwoven fabrics, air-laid nonwoven fabrics, spunlace nonwoven fabrics, needle punched nonwoven fabrics, wet nonwoven fabrics, spunbonded nonwoven fabrics, meltblown nonwoven fabrics, chemically bonded nonwoven fabrics, flash spun nonwoven fabrics, and electrostatically spun nonwoven fabrics. In general, nanofibers have a small fiber diameter, so that the strength per single yarn is low, and since sufficient function is expressed with a small basis weight, the basis weight of the fiber sheet used for product processing is low and the sheet strength is low, which has led to a decrease in processability when processed into products. From this viewpoint, the average fiber diameter of the fibers constituting the nonwoven fabric is 2 to 100 μm, preferably 3 to 50 μm, and more preferably 5 to 40 μm. If the average fiber diameter is 2 μm or more, the strength and rigidity deficiencies of the fiber sheet are compensated for, and a laminate having excellent processability into products is obtained, and if it is 100 μm or less, the contact area between the porous layer and the nanofiber sheet is increased, thereby improving peel resistance.
[0032] The components constituting the porous layer are not particularly limited, and examples thereof include polyolefin resins such as polyethylene and polypropylene, polyester resins such as polyethylene terephthalate and polylactic acid, polyamide resins such as nylon 6 and nylon 6,6, polyurethane resins, fluorine resins such as polyvinylidene fluoride and polytetrafluoroethylene, and cellulose materials such as polysulfone, polyethersulfone, cellulose, and cellulose acetate. These may be used alone or in combination of two or more. Among these, from the viewpoint of imparting strength and rigidity to the fiber sheet and improving processability into products, the components constituting the porous layer preferably contain 30% by weight or more of polyolefin resins, polyester resins, or cellulose materials, and more preferably contain 50% by weight or more. In addition, from the viewpoints of processability and ease of availability, the polyolefin resin is preferably polyethylene or polypropylene, the polyester resin is preferably polyethylene terephthalate, and the cellulose material is preferably pulp, cotton, or rayon.
[0033] When the porous layer is a nonwoven fabric, the fibers constituting the nonwoven fabric may be single-component fibers or composite fibers, but composite fibers are preferred because they can improve adhesion to the fiber sheet by post-processing such as heat treatment. The composite fibers may be a blend of multiple components, or may have a composite form such as a concentric sheath-core type, an eccentric sheath-core type, a parallel type, an island-in-the-sea type, or a radial type. In addition, composite fibers may be made of two or more materials having different melting points. Examples of the high melting point component include polypropylene, polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, nylon 6, nylon 6,6, and poly-L-lactic acid, and examples of the low melting point component include low density polyethylene, linear low density polyethylene, high density polyethylene, polyethylene terephthalate copolymer, poly-DL-lactic acid, polypropylene copolymer, and polypropylene. The melting point difference between the high melting point component and the low melting point component of the composite fiber is not particularly limited, but is preferably 15°C or more, more preferably 30°C or more, in order to widen the processing temperature range of the heat treatment.
[0034] The cross-sectional shape of the fibers constituting the nonwoven fabric is not particularly limited, and examples thereof include circular, elliptical, flat, semicircular, star-shaped, triangular, rectangular, pentagonal, multi-lobed, array-shaped, T-shaped, and horseshoe-shaped. From the viewpoint of improving adhesion to the fiber sheet, however, elliptical, flat, or semicircular cross-sectional shapes are preferable. A nonwoven fabric containing fibers having an elliptical, flat, or semicircular cross-sectional shape can be obtained, for example, by forming fibers having an elliptical, flat, or semicircular cross-sectional shape into a web and then bonding them with heat or an adhesive, or by subjecting a nonwoven fabric composed of fibers having a circular cross-sectional shape to a thermal calendaring process. In addition, the surface of the fiber may be treated with a fiber finishing agent within a range that does not impair the effects of the present invention, which can impart functions such as hydrophilicity, water repellency, antistatic properties, surface smoothness, and abrasion resistance. In addition, a plurality of fibers having different fiber diameters and properties may be laminated or mixed within a range that does not impair the effects of the present invention.
[0035] The porous layer may contain additives such as antibacterial agents, deodorants, antistatic agents, conductive materials, fluorescent materials, smoothing agents, hydrophilic agents, water repellents, antioxidants, weather resistance agents, surfactants, and charge stabilizers as needed, within the scope of the invention.
[0036] The porous layer is not particularly limited, and may have an uneven shape such as embossed points or shaping. Generally, a porous layer having an uneven shape such as embossed points or shaping is easily peeled off because of a small contact area with the nanofiber sheet, but the fiber sheet of the present invention has excellent adhesion between the porous layer and the nanofiber sheet due to the protective fiber sheet, so that the porous layer and the nanofiber sheet are easily integrated even if they have an uneven shape such as embossed points or shaping.
[0037] The basis weight of the porous layer is not particularly limited, but is preferably 5 to 150 g / m 2 and preferably 10 to 105 g / m 2 More preferably, the thickness is 15 to 85 g / m 2 It is more preferable that the weight of the porous layer is 5 g / m 2 If the fiber sheet composite has a thickness of 150 g / m or more, the rigidity of the fiber sheet composite can be increased and the processability into products can be improved. 2 If it is below this level, the properties derived from the nanofibers are less likely to be hindered.
[0038] The thickness of the porous layer is not particularly limited, but is preferably 0.01 to 1 mm, and more preferably 0.05 to 0.8 mm. Within the above range, the rigidity of the fiber sheet composite can be increased, and the processability into products can be improved.
[0039] The specific volume of the porous layer is not particularly limited, but is preferably 1 to 10 cm 3 / g, and 2 to 8 cm 3 / g, and 3 to 6 cm 3 / g. It is more preferable that the specific volume of the porous layer is 10 cm 3 If the thickness is less than 1 cm / g, satisfactory peel resistance is obtained. 3 / g or more, the properties derived from the nanofibers are less likely to be hindered.
[0040] <Fiber sheet> The fiber sheet of the present invention is formed by laminating the above-mentioned nanofiber sheet, a protective fiber sheet, and a porous layer in this order. By including the protective fiber sheet between the nanofiber sheet and the porous layer, the fiber sheet has excellent adhesion, preventing deformation or tearing of the surface of the nanofiber sheet during pleating, and making it possible to produce a fiber sheet with high productivity.
[0041] The basis weight of the fiber sheet is not particularly limited, but is preferably 5 to 200 g / m 2 It is preferable that the thickness is 10 to 150 g / m 2 More preferably, the thickness is 15 to 120 g / m 2 It is more preferable that the weight of the fiber sheet is 5 g / m 2 If the fiber sheet has a hardness of 200 g / m or more, the rigidity of the fiber sheet is increased and the processability into products can be improved. 2 If the thickness is less than 2 mm, the fiber sheet can be lightweight when used as, for example, a filter medium, a mask, a sound absorbing material, etc. The thickness of the fiber sheet is not particularly limited, but is preferably 0.01 to 2 mm, more preferably 0.05 to 1.5 mm, and even more preferably 0.06 to 1 mm. If the thickness of the fiber sheet is 0.01 mm or more, the rigidity of the fiber sheet is increased and the processability into products can be improved, and if the thickness is 2 mm or less, the space can be saved when used as, for example, a filter medium, a mask, a sound absorbing material, etc.
[0042] The fiber sheet may be subjected to antistatic treatment, water-repellent treatment, hydrophilic treatment, antibacterial treatment, ultraviolet absorbing treatment, near-infrared absorbing treatment, electret treatment, etc., depending on the purpose, so long as the effects of the present invention are not significantly impaired. The fiber sheet composite of the present invention has sufficient mechanical strength and appropriate rigidity, and also exhibits the effect of excellent secondary processability, such as electrostatic treatment, water-repellent treatment, hydrophilic treatment, antibacterial treatment, ultraviolet absorbing treatment, near-infrared absorbing treatment, or electret treatment.
[0043] The fiber sheet of the present invention has excellent adhesion and mechanical strength between the nanofiber sheet and the porous layer, and contains few components such as adhesives, so it can be suitably used as a high-performance filter material, although it is not particularly limited.The object of filtration is not particularly limited, and it may be an air filter material used in air conditioners and clean rooms, or a liquid filter material used to filter wastewater, paint, abrasive particles, etc.The type of filter is also not particularly limited, and it may be a flat membrane filter, a pleated filter, or a depth filter rolled up into a cylindrical shape.
[0044] When the fiber sheet is used as a filter medium for an air filter, the pressure loss when air is passed through at a flow rate of 5.3 cm / sec is preferably 10 to 1500 Pa, more preferably 20 to 300 Pa, and even more preferably 50 to 200 Pa. If the pressure loss is 10 Pa or more, a sufficient collection efficiency% (=(1-transmittance)×100) can be obtained, and if it is 1500 Pa or less, the air filter has high breathability, and effects such as reduced power consumption and reduced load on the fan are achieved. In addition, when air containing particles with a particle diameter of about 0.1 to 0.3 μm is passed through at 5.3 cm / sec, the collection efficiency of the particles is preferably 80% or more, more preferably 90% or more. Furthermore, the QF value (=log(1-collection efficiency / 100) / pressure loss×1000) is preferably 12 or more, more preferably 15 or more. The QF value is a value used as an index indicating the magnitude of the collection performance of an air filter, and the higher the QF value, the higher the performance.
[0045] <Layer structure of fiber sheet> The layer structure of the fiber sheet may be porous layer / protective fiber sheet / nanofiber sheet or nanofiber sheet / protective fiber sheet / porous layer.
[0046] <Method of manufacturing fiber sheet> The fiber sheet of the present invention is not particularly limited, and examples thereof include a method of directly forming a nanofiber sheet on a porous layer laminate having a protective fiber sheet formed on a porous layer, a method of preparing a porous layer laminate and a nanofiber sheet, and performing a thermocompression treatment using a heated flat roll or embossing roll, or a bonding treatment using a hot melt agent or a chemical adhesive, but from the viewpoint of simplifying the manufacturing process, a method of directly forming a nanofiber sheet on a porous layer laminate is preferred. The method of forming a protective fiber sheet on a porous layer is not particularly limited, and an airlaid method, a papermaking method, a spunbond method, a meltblown method, a centrifugal spinning method, an electrostatic spinning method, etc. can be used, but from the viewpoint of forming a protective fiber sheet with a small fiber diameter and a uniform fiber diameter, it is preferable to form it by an electrostatic spinning method. In addition, the method of forming a nanofiber sheet on a protective fiber sheet is not particularly limited, but from the viewpoint of making the diameter of the nanofibers small and uniform, it is preferable to form it by an electrostatic spinning method.
[0047] The electrostatic spinning method will be described in detail below, but is not limited thereto.
[0048] The electrostatic spinning method is a method in which a spinning solution is discharged and an electric field is applied to the discharged spinning solution to form fibers of a very small fiber diameter on a collector. For example, there are a method in which a spinning solution is extruded from a nozzle and an electric field is applied to spin the solution, a method in which a spinning solution is foamed and an electric field is applied to spin the solution, and a method in which a spinning solution is introduced onto the surface of a cylindrical electrode and an electric field is applied to spin the solution.
[0049] The spinning solution is not particularly limited as long as it has spinnability. For example, a solution in which the above-mentioned polymer is dispersed or dissolved in a solvent, or a solution in which the polymer is melt-kneaded by heat or laser irradiation, etc. can be used. From the viewpoint of making the average fiber diameter of the nanofibers and the protected fibers small and uniform, it is preferable to use a spinning solution in which a polymer is dissolved in a solvent.
[0050] The solvent for dispersing or dissolving the polymer is not particularly limited, and examples thereof include water, methanol, ethanol, propanol, acetone, methyl ethyl ketone, tetrahydrofuran, cyclohexanone, γ-butyrolactone, N,N-dimethylformamide, N,N-dimethylacetamide, N,N-dimethylpropionamide, dimethylsulfoxide, N-methyl-2-pyrrolidone, triethyl phosphate, propylene glycol monomethyl ether, diethylene glycol ethyl methyl ether, toluene, xylene, pyridine, formic acid, and acetic acid. Examples of the solvent include acid, tetrahydrofuran, dichloromethane, chloroform, and 1,1,1,3,3,3-hexafluoroisopropanol, but from the viewpoint of the solubility of the vinylidene fluoride polymer and the vinylidene fluoride copolymer, it is preferable to use N,N-dimethylformamide, N,N-dimethylacetamide, N,N-dimethylpropionamide, dimethylsulfoxide, N-methyl-2-pyrrolidone, triethylphosphate, acetone, methyl ethyl ketone, tetrahydrofuran, cyclohexanone, or γ-butyrolactone. These solvents may be used alone or in combination of two or more in any ratio.
[0051] The additives such as the above-mentioned conductive agent and water repellent agent are not particularly limited, but are preferably contained in the spinning solution. By containing the additive in the spinning solution, the additive can be uniformly added to the nanofiber, and various functions can be added without going through an additive addition process, which is preferable. The content of the additive may be appropriately selected depending on the type and the desired effect, and it is preferable that the content of the additive is 0.001 to 5 wt % with respect to the spinning solution, since an effect commensurate with the use can be obtained.
[0052] The method for preparing the spinning solution is not particularly limited, and examples thereof include stirring and ultrasonic treatment. The order of mixing is also not particularly limited, and each component may be mixed simultaneously or sequentially. When preparing the spinning solution by stirring, the stirring temperature and stirring time are not particularly limited as long as the polymer can be sufficiently mixed, and for example, stirring may be performed at 40 to 120°C for about 1 to 24 hours.
[0053] The viscosity of the spinning solution is not particularly limited, but is preferably 10 to 5000 cP, more preferably 20 to 2000 cP, and even more preferably 50 to 1000 cP. If the viscosity of the spinning solution is 10 cP or more, good spinnability and spinning stability can be obtained, and if it is 1000 cP or less, preparation of the spinning solution and discharge during electrostatic spinning are easy. The viscosity of the spinning solution can be adjusted by appropriately changing the molecular weight and concentration of the polymer, the type of solvent, and the mixing ratio.
[0054] The temperature of the spinning solution may be room temperature, or may be, for example, 0 to 200° C. while heating or cooling. As a method for discharging the spinning solution, for example, a method of discharging the spinning solution filled in a syringe or tank from a nozzle using a pump can be mentioned. The inner diameter of the nozzle is not particularly limited, and can be 0.1 to 1.5 mm, for example. In addition, the amount of the spinning solution delivered per hole is not particularly limited, and can be 0.1 to 20 mL / hr, for example.
[0055] The method of applying an electric field is not particularly limited as long as it is a method that can perform stable electrostatic spinning. For example, a high voltage may be applied to the nozzle or spinning solution and the collector may be grounded. The voltage to be applied is not particularly limited as long as it can form fibers and can perform stable spinning, and can be 5 to 100 kV, for example. The distance between the nozzle and the collector (spinning distance) is not particularly limited as long as the solvent is sufficiently volatilized, and can be 50 to 1000 mm, for example. The electric field strength is not particularly limited, but is preferably 1 to 10 kV / cm, and more preferably 2 to 5 kV / cm. If the electric field strength is 1 kV / cm or more, the peel resistance between the fiber sheets and between the fiber sheet and the porous layer can be improved, and if it is 10 kV / cm or less, the porosity of the fiber sheet can be increased, making it easier to achieve both a high specific surface area and high air permeability. The material of the collector is not particularly limited as long as it can collect the electrostatically spun fibers, and a conductive material such as a metal can be suitably used. The shape of the collector is not particularly limited, but it is preferable to use a conveyor-shaped collector for continuous production.
[0056] The atmospheric temperature and humidity during electrostatic spinning are preferably controlled, and the ranges are not particularly limited, but may be, for example, 20 to 30°C and 25 to 45 RH%. This temperature and humidity range allows for relatively easy control throughout the year, and changes in the spinning behavior and physical properties of the obtained fiber sheet due to changes in the atmospheric temperature and humidity are unlikely to occur.
[0057] The pressure loss (flow velocity 5.3 cm / sec) of the intermediate body in which a protective fiber sheet is formed on a porous layer (hereinafter sometimes referred to as a porous layer laminate) is not particularly limited, but in order to maintain the breathability of the fiber sheet, it is preferably 50 Pa or less, more preferably 20 Pa or less, and even more preferably 10 Pa or less.
[0058] When the fiber sheet includes two or more layers of nanofiber sheets, an example of the method is electrostatic spinning using a conveyor-like collector and arranging two or more rows of nozzles in the conveyor's traveling direction. In this case, from the viewpoint of uniformity of the fiber sheet, it is preferable to perform electrostatic spinning while traversing the nozzle in a direction perpendicular to the conveyor's traveling direction (the width direction of the fiber sheet). In addition, the spinning solution discharged from each row may be the same or different. When the spinning solution is the same, a laminate of nanofiber sheets having the same physical properties is obtained, and when the spinning solution is different, a laminate of nanofiber sheets having different physical properties is obtained. For example, the content of additives such as a conductive agent or a water repellent, the concentration of the polymer, the type of solvent, etc. can be appropriately changed according to the desired physical properties.
[0059] The fiber sheet of the present invention may be subjected to heat treatment by circulating hot air or radiant heat in order to further improve the peel resistance between the nanofiber sheet and the porous layer. In the case of thermocompression treatment by a flat roll or an embossing roll, the fiber sheet is melted and formed into a film, or tears occur around the embossing point, resulting in considerable damage. For example, if there is damage, when the fiber sheet is used as an air filter medium, the performance is likely to be reduced, such as the air permeability being reduced by melting and forming into a film, or the collection characteristics being reduced by tearing. In addition, in the case of adhesion by a hot melt agent or a chemical adhesive, the components fill the interfiber voids of the fiber sheet, which also tends to cause a decrease in performance. On the other hand, when heat treatment by circulating hot air or radiant heat is performed, there is almost no damage to the fiber sheet, and sufficient peel resistance can be imparted, which is preferable.
[0060] When heat treatment is performed using circulating hot air or radiant heat, the fibers constituting the porous layer preferably include heat-adhesive composite fibers, although there is no particular limitation thereto. The melting point of the low-melting point component of the heat-adhesive composite fiber is preferably at least 20° C. lower than the melting point of the polymer used in the present invention, more preferably at least 30° C. lower, from the viewpoint of widening the range of heat treatment processing conditions. The heat treatment temperature using circulating hot air or radiant heat is also not particularly limited, but can be set within a range below the melting point of the polymer used in the present invention while observing the balance between peel resistance and the desired properties. EXAMPLES
[0061] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. The measurement methods or definitions of the physical properties shown in the examples are shown below.
[0062] <Melting point of the polymer that composes the nanofiber> Using a PerkinElmer DSC measuring device (DSC8500), measurements were performed in the temperature range from room temperature to 230°C, at a temperature increase / decrease rate of 10°C / min, in a nitrogen atmosphere, and the temperature of the melting peak top in the second run was taken as the melting point (°C).
[0063] <Average fiber diameter of nanofibers, protective fibers, and fibers constituting the porous layer> Using a scanning electron microscope (SU-8000) manufactured by Hitachi, Ltd., the surfaces of the nanofiber sheet, protective fiber sheet, and porous layer were observed at 500 to 30,000 magnifications, and the fiber diameters of 50 or more fibers were measured using image analysis software (Scion Image 4.0.3.2), and the average value was taken as the average fiber diameter.
[0064] <Filter performance> Using a TSI filter efficiency automatic detection device (Model 8130), the pressure drop and collection efficiency were measured when the sample was passed through salt (at a constant flow rate of 5.3 cm / sec).
[0065] <Shore hardness A or D> The Shore hardness A or D was measured using a digital rubber hardness tester DD5 manufactured by Kobunshi Keiki Co., Ltd. in accordance with the measurement methods of ISO7619 and ASTM D 2240.
[0066] <Rockwell hardness> The Rockwell hardness was measured using a Mitutoyo Rockwell hardness tester (HR-524) in accordance with the measurement method of JIS K 7202.
[0067] <Workability> When the following pleating process was performed, the degree of adhesion between the nanofiber sheet and the porous layer, and deformation or tearing of the nanofiber sheet surface were visually observed, and the processability was evaluated on a three-level scale of ◎, ○, and × as follows. ⊚: No peeling between the nanofiber sheet and the porous layer, and no deformation or tearing of the surface of the nanofiber sheet occurred, and this is at a satisfactory level. ○: Slight deformation of the nanofiber sheet surface occurs, but no tearing or peeling between the nanofiber sheet and the porous layer occurs, and this is at an acceptable level. ×: Peeling off of the nanofiber sheet and the porous layer occurs, or the surface of the nanofiber sheet is torn, the properties are deteriorated, and the sheet cannot be processed into a product. (pleats) Using a high-speed multi-reciprocating folding machine manufactured by Hoptec Co., Ltd., the fiber sheet was pleated to a folding height of 10 to 11 mm at a folding speed of 20 to 30 pleats per minute, and the pleats were then pressed and molded at 0.08 MPa for 20 minutes on a table set at 50°C.
[0068] [Production Example 1] A spinning solution was prepared by mixing 15 parts by weight of an ester-based polyurethane manufactured by DIC Covestro Polymer Co., Ltd. (product name: PANDEX (registered trademark) T1180, Shore hardness: A80), 85 parts by weight of N,N-dimethylacetamide, and 0.025 parts by weight of sodium dodecyl sulfate as a conductivity imparting agent. A conveyor-type collector was used as the collection section, and a nonwoven fabric (thickness: approximately 0.3 mm, basis weight: approximately 80 g / m) made of thermally adhesive composite fiber (average fiber diameter: approximately 40 μm) containing polyethylene terephthalate copolymer and polyethylene terephthalate was attached to the collector surface. 2 ) was attached as a porous layer. Next, one nozzle with an inner diameter of 0.3 mm and 12 holes was installed, and while the nozzle was traversed in a direction perpendicular to the traveling direction of the conveyor, electrostatic spinning was performed on the porous layer to laminate a protective fiber sheet, and a laminate with the porous layer was obtained. The spinning conditions in this production example were: the amount of liquid sent per hole to each nozzle using a pump was 0.8 mL / hr, the applied voltage was 45 kV, the spinning distance was 100 mm, the nozzle traverse width was 170 mm, the traverse speed was 150 mm / sec, the temperature and humidity of the spinning space were 25°C and 30 RH%, and the basis weight of the protective fiber sheet was 0.1 g / m 2 The feeding speed of the porous layer by the conveyor-like collector was adjusted so that the electrostatic spinning was performed. The average fiber diameter of the protective fibers constituting the protective fiber sheet was 20 nm, and the pressure loss of the porous layer laminate was 4.5 Pa.
[0069] [Production Example 2] A spinning solution was prepared in the same manner as in Production Example 1, except that the ingredients were changed to 10 parts by weight of an ester-based polyurethane manufactured by BASF Japan Ltd. (product name: Elastollan (registered trademark) C80A, Shore hardness: A82), 54 parts by weight of N,N-dimethylformamide, and 36 parts by weight of tetrahydrofuran. Next, the same spinning conditions as in Production Example 1 were used except that the amount of liquid sent per nozzle using a pump was changed to 1.2 mL / hr, and the basis weight of the protective fiber sheet was 0.1 g / m 2 The porous layer laminate was obtained by adjusting the feeding speed of the conveyor-like collector so that the average fiber diameter of the protective fibers was 200 nm, and the pressure loss of the porous layer laminate was 4.0 Pa.
[0070] [Production Example 3] A spinning solution was prepared in the same manner as in Production 1, except that 15 parts by weight of ester polyurethane manufactured by DIC Covestro Polymer Co., Ltd. (trade name: PANDEX (registered trademark) 1190, Shore hardness: A90 to A95) and 85 parts by weight of N-dimethylacetamide were used. Next, the same spinning conditions as in Production Example 1 were used except that the amount of liquid sent per nozzle using a pump was changed to 1.2 mL / hr, and the basis weight of the protective fiber sheet was 0.1 g / m 2 The porous layer laminate was obtained by adjusting the feeding speed of the conveyor-like collector so that the average fiber diameter of the protective fibers was 30 nm, and the pressure loss of the porous layer laminate was 6.3 Pa. [Production Example 4] A spinning solution was prepared in the same manner as in Production Example 1, except that the components were changed to 15 parts by weight of a polyurethane resin manufactured by DIC Covestro Polymer Co., Ltd. (product name: Elastollan (registered trademark) C80A, Shore hardness: A82), 51 parts by weight of N,N-dimethylacetamide, and 34 parts by weight of tetrahydrofuran. Next, the same spinning conditions as in Production Example 1 were used except that the amount of liquid sent per nozzle using a pump was changed to 1.2 mL / hr, and the basis weight of the protective fiber sheet was 0.1 g / m 2 The conveyor-like collector was used to adjust the speed at which the porous layer was fed, so that the porous layer laminate had one protective sheet laminated thereon. The average fiber diameter of the protective fibers was 2000 nm, and the pressure loss of the porous layer laminate was 3.5 Pa. [Production Example 5] A spinning solution was prepared in the same manner as in Production Example 1, except that the spinning solution was changed to a mixture of 16 parts by weight of vinylidene fluoride homopolymer manufactured by Solvay Specialty Polymers (product name: Solef6010 (Solef is a registered trademark), melting point: 170°C, Shore hardness: D73 to D80), 84 parts by weight of N,N-dimethylacetamide, and 0.05 parts by weight of sodium dodecyl sulfate as a conductivity imparting agent. Next, the same spinning conditions as in Production Example 1 were used, and the nanofiber sheet had a basis weight of 0.1 g / m 2 The feeding speed of the porous layer by the conveyor-like collector was adjusted so that the porous layer laminate was formed by using a nanofiber sheet instead of a protective fiber sheet. The average fiber diameter of the nanofibers was 100 nm, and the pressure loss of the porous layer laminate was 5.2 Pa.
[0071] [Example 1] A spinning solution was prepared by mixing 18.5 parts by weight of vinylidene fluoride homopolymer manufactured by Solvay Specialty Polymers (Solef 6010; melting point: 170°C (Solef is a registered trademark)), 1.5 parts by weight of vinylidene fluoride copolymer manufactured by Solvay Specialty Polymers (Kynar Flex 2500; melting point: 125-177°C, Kynar Flex is a registered trademark), 80 parts by weight of N,N-dimethylacetamide, and 0.05 parts by weight of sodium dodecyl sulfate as a conductivity imparting agent. A conveyor-type collector was used as a collector, and the porous layer laminate obtained in Production Example 1 was attached to the collector surface. Next, two nozzles with an inner diameter of 0.3 mm and 12 holes were installed so that the distance between each nozzle was 380 mm in the conveyor travel direction, and electrostatic spinning was performed on the protective fiber sheet of the porous layer laminate while the nozzles were traversed in a direction perpendicular to the conveyor travel direction, to obtain a fiber sheet (nanofiber sheet / nanofiber sheet / protective fiber sheet / porous layer four-layer structure) in which two nanofiber sheets and a porous layer laminate were laminated. The spinning conditions in this example were: the amount of liquid sent per hole to each nozzle using a pump was 1.6 mL / hr, the applied voltage was 45 kV, the spinning distance was 100 mm, the nozzle traverse width was 170 mm, the traverse speed was 150 mm / sec, the temperature of the spinning space was 25° C., and the humidity was 30 RH%, and the nanofiber sheet had a basis weight of 1.0 g / m2 The feeding speed of the porous layer laminate by the conveyor-like collector was adjusted so that the nanofibers were not fuzzed. The average fiber diameter of the nanofibers was 110 nm, and the filter performance of the fiber sheet was a pressure drop of 150 Pa and a collection efficiency of 99.99%. Furthermore, no deformation or tearing of the nanofiber sheet surface or peeling between the nanofiber sheet and the porous layer was observed during pleating. The filter performance after processing was a pressure drop of 161 Pa and a collection efficiency of 99.98%, with almost no decrease in collection performance.
[0072] [Example 2] A spinning solution was prepared by mixing 20 parts by weight of vinylidene fluoride homopolymer manufactured by Solvay Specialty Polymers (product name: Solef 6010; melting point: 170°C (Solef is a registered trademark)), 80 parts by weight of N,N-dimethylacetamide, and 0.05 parts by weight of sodium dodecyl sulfate as a conductivity imparting agent. A fibrous sheet was obtained in the same manner as in Example 1, except that the porous layer laminate obtained in Production Example 2 was used. The average fiber diameter of the nanofibers was 110 nm, and the filter performance of the fiber sheet was a pressure drop of 149 Pa and a collection efficiency of 99.98%. In addition, no tears occurred on the surface of the nanofiber sheet during pleating. The filter performance after processing was a pressure drop of 158 Pa and a collection efficiency of 99.94%, with almost no decrease in collection performance.
[0073] [Example 3] A fibrous sheet was obtained in the same manner as in Example 2, except that the porous layer laminate obtained in Production Example 3 was used. The average fiber diameter of the nanofibers was 110 nm, and the filter performance of the fiber sheet was a pressure drop of 151 Pa and a collection efficiency of 99.99%. Furthermore, no peeling occurred between the nanofiber sheet and the porous layer or the surface of the nanofiber sheet during pleating. The filter performance after processing was a pressure drop of 164 Pa and a collection efficiency of 99.98%, with almost no decrease in collection performance. [Example 4] A fibrous sheet was obtained in the same manner as in Example 2, except that the porous layer laminate obtained in Production Example 4 was used. The average fiber diameter of the nanofibers was 110 nm, and the filter performance of the fiber sheet was a pressure drop of 145 Pa and a collection efficiency of 99.98%. Furthermore, no tears occurred on the surface of the nanofiber sheet during pleating. Peeling between the nanofiber sheet and the porous layer was observed, but this was within the acceptable range. The filter performance after processing was a pressure drop of 154 Pa and a collection efficiency of 99.96%, and the decrease in collection performance was within the acceptable range.
[0074] [Comparative Example 1] A fiber sheet (three-layer structure of nanofiber sheet / nanofiber sheet / porous layer) was obtained in the same manner as in Example 2, except that the porous layer used in Production Example 1 was attached to the collector surface instead of the porous layer laminate. The average fiber diameter of the nanofibers was 110 nm, and the filter performance of the fiber sheet was a pressure drop of 152 Pa and a collection efficiency of 99.98%, but the filter performance after processing was a pressure drop of 163 Pa and a collection efficiency of 99.87%, showing a significant decrease in collection performance. When the fiber sheet was passed through the processing line, ruptures were confirmed in the nanofibers in the top layer of the fiber sheet, resulting in a decrease in filter performance.
[0075] [Comparative Example 2] A spinning solution was prepared by mixing 15 parts by weight of a thermoplastic urethane polymer (product name: PANDEX (registered trademark) T1190) manufactured by DIC Covestro Polymer Co., Ltd., 85 parts by weight of N-dimethylacetamide, and 0.025 parts by weight of sodium dodecyl sulfate as a conductivity-imparting agent. A conveyor-like collector was used as the collection section, and a protective fiber sheet was electrostatically spun onto the fiber sheet under the same spinning conditions as in Production Example 3, except that the fiber sheet obtained in Comparative Example 1 was attached to the collector surface, to obtain a fiber sheet (four-layer structure of protective fiber sheet / nanofiber sheet / nanofiber sheet / porous layer). The filter performance of the fiber sheet was a pressure drop of 159 Pa and a collection efficiency of 99.96, but the filter performance after processing was a pressure drop of 182 Pa and a collection efficiency of 99.91%, with an increased pressure drop. When the fiber sheet was passed through the processing line, adhesion of the fibers in the top layer of the fiber sheet was confirmed, resulting in a decrease in filter performance. [Comparative Example 3] A fiber sheet (four-layer structure of nanofiber sheet / nanofiber sheet / nanofiber sheet / porous layer) was obtained in the same manner as in Example 2, except for using the porous layer laminate obtained in Production Example 5. When the nanofiber sheet was produced, fluffing occurred on the nanofiber surface. The average fiber diameter of the nanofibers that make up the nanofiber sheet was 110 nm, and the filtering performance of the fiber sheet was a pressure drop of 148 Pa and a collection efficiency of 99.98%, but after processing, the filtering performance was significantly reduced, with a pressure drop of 157 Pa and a collection efficiency of 99.86%. When the fiber sheet was passed through the processing line, breakage of the fibers in the top layer of the fiber sheet was confirmed, resulting in a reduction in filtering performance.
[0076] Table 1 shows the production conditions and physical properties of the porous layer laminate.
[0077] [Table 1]
[0078] [Table 2]
[0079] [Table 3] [Industrial Applicability]
[0080] The fiber sheet of the present invention has excellent adhesion between the nanofiber sheet and the porous layer without impairing the inherent properties of the nanofibers, and therefore can be provided with high productivity and good operability without undergoing an integration process such as bonding or calendaring. Therefore, the fiber sheet can be suitably used as filter media, sound absorbing materials, masks, waterproof and moisture permeable membranes, secondary battery separators, sensor materials, cell culture substrates, and the like.
Claims
1. A fiber sheet in which a nanofiber sheet containing nanofibers, a protective fiber sheet containing protective fibers, and a porous layer are laminated in this order, wherein the nanofibers have an average fiber diameter of 20 to 1000 nm, and a polymer constituting the protective fibers satisfies at least one selected from the following (1) to (3): (1) Rockwell hardness R110 or less (2) Shore hardness A100 or less (3) Shore hardness D70 or less
2. The fiber sheet according to claim 1 , wherein the polymer constituting the protective fibers includes at least one polymer selected from the group consisting of thermoplastic urethane polymers, thermoplastic urea polymers, and vinyl acetal polymers.
3. The fiber sheet according to claim 1 or 2, wherein the polymer constituting the nanofibers comprises a vinylidene fluoride polymer.
4. The fiber sheet according to claim 1 or 2, wherein the protective fibers have an average fiber diameter of 20 to 5000 nm.
5. The fiber sheet according to claim 1 or 2, comprising two or more layers of the nanofiber sheet.
6. 3. The method for producing a fiber sheet according to claim 1 or 2, comprising the steps of electrostatically spinning the protective fiber sheet onto the porous layer, and electrostatically spinning a nanofiber sheet onto the protective fiber sheet.
7. The method for producing a fiber sheet according to claim 6, further comprising a step of heat treating the nanofiber sheet with circulating hot air or radiant heat after the step of electrostatically spinning the nanofiber sheet.
8. A filter medium comprising the fiber sheet according to claim 1 or 2.
Citation Information
Patent Citations
Laminate and filter material
JP2007030175A
Fiber sheet and fiber product using the same
JP2015045114A
Transgenic poaceae plant, seed thereof, or production method of processed goods of seed
JP2015057950A
Cited By
Fluorine-free polyimide-based film and preparation method thereof
CN120401124A